Josip Broz in Omsk. To the history of Russian Revolution, Russian Civil War and Socialist Construction - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The fact of the participation of Josip Broz in Russian Revolution 1917–1922 and Russian Civil War in Siberia in different years had a different assessment. However, it is in the Omsk period of life of the permanent leader of the Socialist Federal Republic of Yugoslavia that it is advisable to seek answers to questions from historians and journalists related to the intricacies of his personal life and the choice of political course. The past 20th century was filled with the search for models of socio-economic reorganization: from various variants of «fascism» to socialist reorganization of society. One of those is the building of market socialism in nonaligned Yugoslavia. This experience is associated with the name of the President of the SFRY, Comrade Tito